Spontaneous Slowing and Regressing of Tumor Growth in Childhood/Adolescent Papillary Thyroid Carcinomas Suggested by the Postoperative Thyroglobulin-Doubling Time. (16th May 2018) - Kasahara, Toshihiko; Miyauchi, Akira; Kudo, Takumi; Nishihara, Eijun; Ito, Mitsuru; Ito, Yasuhiro; Kihara, Minoru; Miya, Akihiro
Abstract : Background . Children and adolescents with papillary thyroid carcinomas (PTCs) have generally excellent prognoses despite their frequent extended disease. The tumor growth of young patients' PTCs might show spontaneous slowing postoperatively. We compared young PTC patients' postoperative thyroglobulin-doubling time (Tg-DT) with their preoperative hypothetical tumor volume-doubling time (hTV-DT). Methods . Fourteen PTC patients aged ≤18 years who underwent total thyroidectomy at Kuma Hospital in 1998–2016 had biochemically persistent disease postoperatively. We calculated their Tg-DTs and estimated their preoperative TV-DTs with the tumor size and the patient's age at surgery, presuming that a single cancer cell was present at the patient's birth. Results . Twelve patients had positive Tg-DTs ranging from 2.0 to 147 years, and the remaining two had negative Tg-DTs, indicating slow growth or even regression. The hTV-DTs were 0.3–0.6 years (median 0.5 years), which were significantly shorter than the Tg-DTs (p < 0.001 ), indicating much faster growth preoperatively. The analyses of the nine patients without radioactive iodine administration (RAI) gave similar results (p < 0.01 ). Conclusions . Irrespective of RAI, the patients' postoperative Tg-DTs were significantly longer than their preoperative hTV-DTs and were negative values in two patients, indicating that the growth of these young patients' PTCs had spontaneously slowed or even regressed postoperatively.